Instrument for Social Support in Physical Education - Diky Hadyansah; Supriadi, Dedi (Journal of Physical and Outdoor Education, 2023)
The purpose of this research is to develop a social support instrument in physical education learning. This research is an R&D research and development from Borg & Gall (1983) which divides the development stages into 10 stages, namely 1) data collection for preliminary research 2) Development planning is carried out by determining the objectives and preparing a trial plan. 3) Developing initial products, which are then evaluated by 2 expert judgment and make product revisions 4) Small group trials. 5) Product revision 6) Field trial (medium group). 7) Conduct product revision 8) Field trial (large group). 9) Conducting the final stage revision 10) Making a research report. The population in this study were public high school students in Bandung City aged 15-18 years. The research sample was 241 students who were taken using random sampling technique. Data collection in this study using a questionnaire. The analysis used Exploratory factor analysis (EFA) technique and continued with Confirmatory Factor Analysis (CFA) technique. The reliability test results show a Cronbach's Alpha value of 0.926. Because the value is above 0.6, it can be concluded that the measuring instrument in this study is reliable and has good construct validity and reliability quality.